Senegal : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper for Senegal reports that reforms of the groundnut sector are an integral part of poverty reduction and growth strategy. To strengthen public finances and instill more efficiency into the groundnut sector, the government has decided to sell the state-owned groundnut processing company and to eliminate the tax and tariff preferences shielding that company from foreign competition. Fiscal decentralization is essentially viewed by the Senegalese authorities as an important tool for raising the efficiency of capital spending and reducing poverty.